2006
DOI: 10.1007/s00268-005-0702-9
|View full text |Cite
|
Sign up to set email alerts
|

Rectus Sheath Hematoma: A Series of Unfortunate Events

Abstract: Rectus sheath hematoma is a rare but important entity in the differential diagnosis of abdominal pain. Interdisciplinary awareness of this condition is essential, as it is frequently difficult to diagnose, leading to delay in treatment or unneeded surgery. Grade 3 hematomas can lead to abdominal compartment syndrome and can be fatal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 27 publications
1
63
0
2
Order By: Relevance
“…[4,5,9] Concordant with the previous reports, the male to female ratio was in favor of females in our series. One possible reason for the sex difference is the disparity in the size, shape and tone of the rectus muscle.…”
Section: Discussionsupporting
confidence: 82%
“…[4,5,9] Concordant with the previous reports, the male to female ratio was in favor of females in our series. One possible reason for the sex difference is the disparity in the size, shape and tone of the rectus muscle.…”
Section: Discussionsupporting
confidence: 82%
“…Duyarlılığı ve özgünlüğü %100'dür. [2,5,14] Rektus kılıf hematomları boyut ve lokalizasyonuna göre 3 tipe ayrılır. [1] Bu sınıflandırma acil tıp hekiminin konsültasyon istemini ve tedavi seçimini belirler (Tablo 1).…”
Section: Discussionunclassified
“…15 Titone et al reported the most common diagnostic errors, such as strangulated hernia (12 %), ovarian cyst twisted (10 %), intestinal obstruction (8 % ), abdominal neoplasm (4 %), perforated colon (4 %) and appendicitis (4 %). 16 The diagnosis of this disease remains elusive, because in the early stages it can simulate an acute abdomen with loss of blood and a lump.…”
Section: 13mentioning
confidence: 99%